Strategy to Enhance Dendritic Cell‐Mediated DNA Vaccination in the Lung. Issue 7 (8th May 2020) - Kim, Yoo C.; Hsueh, Henry T.; Kim, Namho; Rodriguez, Jason; Leo, Kirby T.; Rao, Divya; West, Natalie E.; Hanes, Justin; Suk, Jung Soo
Abstract: Here, a new paradigm is introduced to promote pulmonary DNA vaccination. Specifically, it is demonstrated that nanoparticles designed to rapidly penetrate airway mucus (mucus‐penetrating particle or MPP) enhance the delivery of an inhaled model DNA vaccine (i.e., ovalbumin‐expressing plasmids) to pulmonary dendritic cells (DC), leading to robust and durable local and trans‐mucosal immunity. In contrast, mucus‐impermeable particles are poorly taken up by pulmonary DC following inhalation, despite their superior ability to mediate DC uptake in vitro compared to MPP. In addition to the enhanced immunity achieved in mucosal surfaces, inhaled MPP unexpectedly provides significantly greater systemic immune responses compared to gold‐standard approaches applied in the clinic for systemic vaccination, including intradermal injection and intramuscular electroporation. It is also shown here that inhaled MPP significantly enhances the survival of an orthotopic mouse model of aggressive lung cancer compared to the gold‐standard approaches. Importantly, it is discovered that MPP‐mediated pulmonary DNA vaccination induces memory T‐cell immunity, particularly the ready‐to‐act effector memory‐biased phenotype, both locally and systemically. The findings here underscore the importance of breaching the airway mucus barrier to facilitate DNA vaccine uptake by pulmonary DC and thus to initiate full‐blown immune responses. Abstract : It is shown that nanoparticles designed to breach the airway mucus barrier markedly enhance the codelivery of antigen‐encoding plasmids and nucleic acid‐based adjuvants to the pulmonary DC, thereby leading to robust and durable immune responses in the lung and beyond to a level unachievable by gold‐standard approaches applied in clinic.